2010
DOI: 10.1177/1046878110378708
|View full text |Cite
|
Sign up to set email alerts
|

Applying Cellular Automata and DEVS Methodologies to Digital Games: A Survey

Abstract: International audienceCellular automata were designed by John von Neumann in the 1940s, as a mathematical abstraction for modeling self-replicating algorithms. Since then, cellular automata have been widely studied theoretically and evolved into multiple variants. In the 1970s, Bernard P. Zeigler proposed a formalism rooted on systems theory principles, named DEVS (discrete-event systems specifications), which paved the way for component-based modeling and simulation and related methodologies. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…An important factor in the original development of simulation techniques was that methods were sought to circumvent problems with the analytical intractability of equations describing nonlinear phenomena in the context of research into thermonuclear weapons at the Los Alamos National Laboratories (Galison, 1996;Keller, 2003). Today, however, the notion is more broadly used and includes application to so-called cellular automata (see, for example, Wainer, Liu, Dalle, & Zeigler, 2010) and agent-or individual-based models in which the solution of equations plays no or at best an attenuated role.…”
Section: What Is a (Computer) Simulation?mentioning
confidence: 99%
“…An important factor in the original development of simulation techniques was that methods were sought to circumvent problems with the analytical intractability of equations describing nonlinear phenomena in the context of research into thermonuclear weapons at the Los Alamos National Laboratories (Galison, 1996;Keller, 2003). Today, however, the notion is more broadly used and includes application to so-called cellular automata (see, for example, Wainer, Liu, Dalle, & Zeigler, 2010) and agent-or individual-based models in which the solution of equations plays no or at best an attenuated role.…”
Section: What Is a (Computer) Simulation?mentioning
confidence: 99%
“…This shows that the participants were able to perform logical thinking and decision making based on the situation. In addition, we found that many participants used a strategy that was similar to the technique applied to improve the performance of CA simulations where cellular space is very large (Wainer et al, 2010). They realized that some of the given lands could be omitted, because they were far from the building areas and they would not be able to construct any buildings according to the rules.…”
Section: Resultsmentioning
confidence: 99%
“…Serious games seem to be an appropriate platform to present CA to adolescents. Previously, Wainer, Liu, Dalle, and Zeigler (2010) presented CA in serious games applications. However, those applications merely simulated natural phenomena from predefined structures and variables.…”
Section: Ca and Rationales For Blockyland Developmentmentioning
confidence: 99%
“…CD++ is a modelling and simulation toolkit that implements DEVS and Cell-DEVS theory (Wainer, 2002). It has been used to solve a variety of complex applications (Wainer et al, 2010;Wainer, 2006). The tool allows models to be defined according to the specifications introduced in the previous section.…”
Section: Devs Toolsmentioning
confidence: 99%
“…If the precondition is not met, then the next rule is evaluated until a rule is satisfied or no more rules are available. As discussed in (Wainer, 2006(Wainer, , 2010, this formalism allows security to be improved and development cost to be reduced thanks to the simulations.…”
Section: Postcondition Delay { Precondition }mentioning
confidence: 99%